Implementasi Program Intensive Course (IC) di Pondok Pesantren Pada Masa Pandemi - Nanda, Laudria; Salsabilla, Aliza; Akmalia, Frida (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
This study aims to determine the implementation of the Intensive Course (IC) program in Islamic boarding schools to identify the challenges, strengths, and weaknesses faced in its execution. The method in this research uses qualitative research exploration. Three data collection techniques were used: in-depth interviews through a semi-structured list of questions developed by related literature, observation, and documentation. The results of this study describe the implementation of the IC program during the pandemic. The challenges in its implementation consist of students, teaching materials, and a relatively short time, the advantages and disadvantages of the learning program. This study only describes one Islamic boarding school in Kediri, namely the Syarif Hidayatullah Islamic Boarding School. These results are helpful as an overview of IC during a pandemic and a reference for future research. This study provides evidence-based research information, especially on its implementation at the Syarif Hidayatullah Islamic boarding school.